EDUCATION AS A VIABLE SOFT POWER INITIATIVE IN NIGERIA’S FOREIGN POLICY IMPLEMENTATION: THE NIGERIAN FOREIGN SERVICE ACADEMY AS A CASE STUDY - Idahosa, Stephen; Makpah, Oyeinbiyeridei; Ikhidero, Solomon; Afolabi, Gbadebo; Adebayo, Kafilat (Revista Inclusiones, 2020)
The paper examines education as an instrument of soft power. It offers the Nigeria’s Foreign Service Academy (FSA) as useful instrument for analysing geopolitical and soft power dynamics which influence and attraction transcend national boundaries, with the aim of ensuring peaceful coexistence across national frontiers. It examines Nigeria’s Afrocentric posture in Africa and its effects particularly on Nigerian citizens abroad. Methodologically, it employs the use of descriptive analysis relying solely on secondary information for data generation and analysis. It concludes that, it would be of Nigeria’s interest to train selected diplomats and young leaders in Africa at the FSA on a short-term basis, by extension provides the needed opportunity for Nigeria to transport and impact ideas of African unity, as well as serve as viable channel for transmitting Nigeria's national interest in ensuring Africa's unity and the value of peace and stability in Africa to young African diplomats/leader.